Çözüldü Diferansiyel Denklem Sistemi - Belirsiz Katsayılar Yöntemi - Laplace Dönüşümü (3 Soru)

Konusu 'Akademik Soru Çözümleri ve Kaynakları' forumundadır ve Şennur tarafından 13 Ocak 2021 başlatılmıştır.

Yüklüyor...
  1. Şennur

    Şennur Üye

    Mesajlar:
    88
    Beğenileri:
    39
    Cinsiyet:
    Bayan
    Screenshot_20210113_110618.jpg Sorularıma yardımcı olabilir misiniz

  2. Benzer Konular: Diferansiyel Denklem
    Forum Başlık Tarih
    Akademik Soru Çözümleri ve Kaynakları Tam Diferansiyel Yapılabilen Denklemlerde İntegrasyon Çarpanı - Kısmi Türev ve İntegrasyon Dün 20:17
    Akademik Soru Çözümleri ve Kaynakları Diferansiyel Denklemler (4 Soru, Üçü Çözüldü, Biri Çözülemedi) ) Dün 16:50
    Akademik Soru Çözümleri ve Kaynakları Bir Özel Çözümü Bilinen Riccati Diferansiyel Denkleminin Başlangıç Değerli Çözümü Dün 13:57
    Akademik Soru Çözümleri ve Kaynakları Diferansiyel Denklem 20 Ocak 2021
    Akademik Soru Çözümleri ve Kaynakları Altıncı Derece Sabit Katsayılı ve Sağ Tarafsız Lineer Diferansiyel Denklem 19 Ocak 2021

  3. Honore

    Honore Yönetici Yönetici

    Mesajlar:
    5.284
    Beğenileri:
    638
    Cinsiyet:
    Bay
    Meslek:
    Müh. (Elk./Bilg.)
    Question - 1
    Period (.) has been used for the decimal point because of the language.

    dx / dt = x' = -0.08·x + 0.02·y
    dy / dt = y' = 0.08·x - 0.08·y
    x(0) = 5, y(0) = 2
    system of initial value problem solution:

    ***
    Differentiating the first equation with regard to t (assumed variable);
    x'' = -0.08·x' + 0.02·y'
    y' is taken from the second equation and used above as follows;
    x'' = -0.08·x' + 0.02·(0.08·x - 0.08·y)....(I)
    Again from the first equation, 0.02·y = x' + 0.08·x ⇒ y = 50·x' + 4x is obtained and substituted into (I);
    x'' = -0.08·x' + 0.02·[ 0.08·x - 0.08·(50x' + 4x) ]
    x'' = -0.08·x' + 0.02·(0.08·x - 4x' - 0.32·x)
    x'' = -0.08·x' + 1.6·[ 10^(-3) ]·x - 0.08·x' - 6.4·[ 10^(-3) ]·x
    x'' + 0.16·x' + 4.8·[ 10^(-3) ]·x = 0....(II)
    Auxiliary equation using derivative operator as r = dx / dt is;
    r^2 + 0.16·r + 4.8·[ 10^(-3) ] = 0
    Roots are r1 = -3 / 25 = -0.12 and r2 = -1 / 25 = -0.12
    x(t) = C1·[ e^(-0.12·t) ] + C2·[ e^(-0.04·t) ]....(III)
    Differentiating (III) gives, x' = -0.12·C1·[ e^(-0.12·t) ] - 0.04·C2·[ e^(-0.04·t) ]....(IV)
    Moving (III) and (IV) to the first equation in the problem;
    -0.12·C1·[ e^(-0.12·t) ] - 0.04·C2·[ e^(-0.04·t) ] = -0.08·{ C1·[ e^(-0.12·t) ] + C2·[ e^(-0.04·t) ] } + 0.02·y
    and after simplification, obtaining y from the equation above;
    y(t) = 2·[ e^(-3t / 25) ]·{ -C1 + C2·[ e^(2t / 25) ] }....(V)
    Applying the initial values as x(0) = 5 and y(0) = 2 in (III) and (V);
    5 = C1 + C2....(VI)
    2 = -2·C1 + 2·C2...(VII)
    Solving the equations (VI) and (VII) yields; C1 = 2 and C2 = 3
    So the complete solution based on (III) and (V) using the coefficients C1 and C2 is;

    x(t) = 2·[ e^(-0.12·t) ] + 3·[ e^(-0.04·t) ]

    y(t) = -4·[ e^(-0.12·t) ] + 6·[ e^(-0.04t) ]


    Check by WolframAlpha:
    [​IMG]
    https://i72.servimg.com/u/f72/19/97/10/39/3difde10.png
    https://www.wolframalpha.com/input/...y / dt = 0.08·x - 0.08·y, x(0) = 5, y(0) = 2
    ---
    Not: Diğer 2 soruya da ilk fırsatta bakacağım.
    Şennur bunu beğendi.
  4. Şennur

    Şennur Üye

    Mesajlar:
    88
    Beğenileri:
    39
    Cinsiyet:
    Bayan
    Çok teşekkür ederim size zahmet olmasın biz biraz hallettik galiba diğer 2 soruyu
    Honore bunu beğendi.
  5. Honore

    Honore Yönetici Yönetici

    Mesajlar:
    5.284
    Beğenileri:
    638
    Cinsiyet:
    Bay
    Meslek:
    Müh. (Elk./Bilg.)
    Rica ederim, lafı mı olurmuş. Peki WolframAlpha ile de kontrol ettiniz mi? :)
    ---
    Question - 2
    y'' + 4y = (x^2)sin(2x) solution with Undetermined Coefficients Method


    Auxiliary equation: r^2 + 4 = 0 ⇒ r = 0 ∓ 2i
    Homogeneous solution: yh(x) = [ e^(0·x) ]·[ C1·cos(2x) + C2·sin(2x) ]
    yh(x) = C1·cos(2x) + C2·sin(2x)....(I)

    Since the part [ e^(0·x) ]·sin(2x) of the right hand side function also coincides with the onefold repeated root (0 ∓ 2i) of the auxiliary equation, the particular solution must be in the form of (assuming a, b, c, d, e, f ∈ R);

    yp(x) = (x^1)·(a·x^2 + b·x + c)·[ e^(0·x) ]·cos(2x) + (x^1)·(d·x^2 + e·x + f)·[ e^(0·x) ]·sin(2x)
    yp(x) = (ax^3 + bx^2 + cx)·cos(2x) + (dx^3 + ex^2 + fx)·sin(2x)....(II)

    First derivative after differentiating and grouping:
    y' = (-2ax^3 - 2bx^2 - 2cx + 3dx^2 + 2ex + f)·sin(2x) + (3ax^2 + 2bx + c + 2dx^3 + 2ex^2 + 2fx)·cos(2x)

    Second derivative after differentiating and polynomially grouping:
    y'' = [ sin(2x) ]·(-12ax^2 - 8bx - 4c - 4dx^3 + 6dx - 4ex^2 + 2e - 4fx) +
    [ cos(2x) ]·(-4ax^3 + 6ax - 4bx^2 + 2b - 4cx + 12dx^2 + 8ex + 4f) and simplifying,

    y'' = [ sin(2x) ]·[ -4d·x^3 + (-12a - 4e)·x^2 + (-8b + 6d - 4f)·x - 4c + 2e ] +
    [ cos(2x) ]·[ -4a·x^3 + (12d - 4b)·x^2 + (6a - 4c + 8e)·x + 2b + 4f ]....(III)

    Substituting (II) and (III) in the equation;
    [ sin(2x) ]·[ -4d·x^3 + (-12a - 4e)·x^2 + (-8b + 6d - 4f)·x - 4c + 2e ] +
    [ cos(2x) ]·[ -4a·x^3 + (12d - 4b)·x^2 + (6a - 4c + 8e)·x + 2b + 4f ] + (4a·x^3 + 4b·x^2 + 4c·x)·cos(2x) +
    (4d·x^3 + 4e·x^2 + 4f·x)·sin(2x) = (x^2)·sin(2x)

    [ sin(2x) ]·[ -4d·x^3 + (-12a - 4e)·x^2 + (-8b + 6d - 4f)·x - 4c + 2e + 4d·x^3 + 4e·x^2 + 4f·x ] +
    [ cos(2x) ]·[ -4a·x^3 + (12d - 4b)·x^2 + (6a - 4c + 8e)·x + 2b + 4f + 4a·x^3 + 4b·x^2 + 4c·x ] = (x^2)·sin(2x)

    [ sin(2x) ]·[ -12a·x^2 + (-8b + 6d)·x - 4c + 2e ] + [ cos(2x) ]·[ 12d·x^2 + (6a + 8e)·x + 2b + 4f ] = (x^2)·sin(2x) and applying the Method of Undetermined Coefficients,

    -12a = 1 ⇒ a = -1 / 12
    -8b + 6d = 0
    -4c + 2e = 0
    12d = 0 ⇒ d = 0
    6a + 8e = 0 ⇒ 6·(-1 / 12) + 8e = 0 ⇒ -1 / 2 + 8e = 0 ⇒ e = 1 / 16
    2b + 4f = 0
    -4c + 2·(1 / 16) = 0 ⇒ c = 1 / 32
    b = d = f = 0

    So yp(x) = y(x) = -(1 / 12)·(x^3)·cos(2x) + (1 / 16)·(x^2)·sin(2x) + (1 / 32)·x·cos(2x)....(IV)

    And the final general solution by summing (I) and (IV),
    y(x) = C1·cos(2x) + C2·sin(2x) - (1 / 12)·(x^3)·cos(2x) + (1 / 16)·(x^2)·sin(2x) + (1 / 32)·x·cos(2x)

    Check by WolframAlpha:
    [​IMG]
    https://i72.servimg.com/u/f72/19/97/10/39/3difde11.png
    https://www.wolframalpha.com/input/?i=y'' + 4y = (x^2)sin(2x)
    Şennur bunu beğendi.
  6. Honore

    Honore Yönetici Yönetici

    Mesajlar:
    5.284
    Beğenileri:
    638
    Cinsiyet:
    Bay
    Meslek:
    Müh. (Elk./Bilg.)
    Her ihtimale karşı yine de yazalım belki başkaları yararlanır:
    ---
    Question - 3
    2x''(t) + 32x = 4sin(4t), x(0) = -1 / 2, x'(0) = 0, solution using Laplace Transform

    ℒ{ x''(t) } + ℒ{ 16x } = ℒ{ 2sin(4t) }
    [ (s^2)·X(s) - s·(-1 / 2) - 0 ] + 16·X(s) = 2·[ 4 / (s^2 + 16) ]
    (s^2 + 16)·X(s) + s / 2 = 8 / (s^2 + 16)
    X(s) + s / [ 2·(s^2 + 16) ] = 8 / [ (s^2 + 16)^2 ]
    X(s) = 8 / [ (s^2 + 16)^2 ] - s / [ 2·(s^2 + 16) ]

    And taking inverse Laplace Transform;
    ℒ^(-1) { X(s) } = ℒ^(-1) { 8 / [ (s^2 + 16)^2 ] - s / [ 2·(s^2 + 16) ] }, referring to the Convolution Theorem for the first rational term (unnecessary details were not written), and the standard information given at the relevant tables for the second term the general solution;

    x(t) = (1 / 16)·[ sin(4t) - 4t·cos(4t) ] - (1 / 2)·cos(4t)

    Check by WolframAlpha:
    [​IMG]
    https://i72.servimg.com/u/f72/19/97/10/39/3difde13.png
    https://www.wolframalpha.com/input/?i=laplace transform x''+16x=2sin(4t),x(0)=-0.5,x'(0)=0
    Şennur bunu beğendi.

Sayfayı Paylaş